Het Nijmeegse Valkhof als monument in het spanningsveld tussen vernieuwing en conservering (Bulletin KNOB, 1997)
Since 1936 people have been pleading for reconstruction of Valkhof castle in Nijmegen, which was demolished in 1796. On Valkhof hill extensive subterranean remnants, two chapels and the oldest public town park in landscape style of the Netherlands are reminiscent of this complex.As a whole it is protected under the Historic Buildings and Ancient Monuments Act, which did not prevent the Valkhof association and a property developer from drawing up a plan aimed at converting the 'historical scenery of Valkhof' into a 'contemporary top location of international pretensions, suitable for market-oriented and public-oriented activities'.A subterranean complex measuring approximately 3000 m2 is to be crowned with a building following the forms and contours of the old castle, so as to reinforce the identity of the town as a European trade centre. With a bare majority the town council of Nijmegen decided to cooperate with the plans, although little is known about the design and details of the castle.Among conservation experts reconstruction of lost monuments is a topical issue, connected with our views on the value of ancient monuments. Starting from the idea that history can be made, in accordance with architects such as Viollet-le-Duc, Cuypers and Rose, reconstruction as in the cases of castles De Haar and Sypestein, may well be possible.On the other hand, thinkers such as Ruskin and Weissman emphasize the unique meaning of the monument as a historical document. According to them history cannot be repeated and the demolition of the castle in 1796 is a historical act as well. When one stresses the visual value of a building, as an architectural design recorded in a series of drawings, reconstruction is possible, just as a piece of music can be performed more than once.In such a manner the lost works of J.J.P. Oud were reconstructed on the basis of drawings. However, this vision denies the passage of the monument through time, resulting in numerous building marks that can no longer be imitated. After all, the emotion evoked by the authentic historical experience is also important.One should ask oneself whether a rebuilt castle can be anything else than a historicizing stage setting, bound to lead to disappointment among its visitors. Reconstruction of lost monuments appears to be possible only if it concerns unique buildings with symbolic value, lost because of a calamity and still taking up a place in the memories of the generations living now.When a large building is constructed in Valkhof park this will entail the permanent destruction of a unique archaeological site. The existing monumental foundations will be irrevocably affected when they are fitted into the new building. Likewise, the essence of the park laid out by J.D. Zocher sr. in 1799 and greatly altered by H. van Lunteren in 1832 will also be lost.This park was deliberately conceived around the ruins, in the spirit of Romanticism, in remembrance of the historical meaning of the castle hill. In the meantime the State Secretary for Education, Culture and Science has resolved against the new construction, for reasons of conservation and archaeology. However, for the time being the initiators are pursuing their plans.